Investigating Helical Hypersurfaces Within 7-Dimensional Euclidean Space - Erhan Güler (Journal of Mathematics)
Differential geometry of a kind of helical hypersurface family that depends on six parameters within the seven-dimensional Euclidean space is explored. The curvatures of these hypersurfaces are determined, and their minimality is examined, along with illustrative examples being provided. Lastly, the Laplace–Beltrami operator for that kind of hypersurfaces is calculated.